THE SEMANTICAL ANALYSIS OF PHRASEOLOGICAL UNITS WITH THE COMPONENT OF CLOTHES IN THE ENGLISH LANGUAGE - Ataxojayev Toxirjon Maxmudjonovich (International Journal of Literature and Language Studies, 2026)
The article investigates the semantic peculiarities of English phraseological units with the component of “clothes”. The research analyzes their denotative and connotative meanings, semantic classification, metaphorical transformation, and linguocultural significance. The study applies descriptive, semantic, componential, and contextual methods of analysis. The article demonstrates that clothing-related phraseological units often express human character, social status, emotions, behavior, morality, and interpersonal relations.